A EXPLORING SENIOR AND NOVICE TEACHERS’ PERSPECTIVES ON DEEP LEARNING: A QUALITATIVE STUDY IN ELEMENTARY SCHOOLS - Jumelan; Galuh Putrining Aji; Erna Yayuk (LPPM STAI Muhammadiyah Probolinggo, 2025)
This qualitative research explores how senior and novice teachers perceive and implement deep learning in Indonesian elementary schools. Employing a case study approach, the study engaged senior teachers with more than 15 years of teaching experience and novice teachers with less than 10 years of experience from Gugus 02 Bina Ilmu, Pringkuku District, Pacitan Regency. Data were gathered through in-depth interviews, classroom observations, and document analysis, then analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal both convergences and divergences in teachers’ understanding of deep learning. Senior teachers tend to define deep learning as comprehensive mastery of core content through structured, teacher-centered instruction that prioritizes stability and discipline. In contrast, novice teachers interpret deep learning as a process that fosters critical thinking, creativity, collaboration, and technology integration aligned with the Kurikulum Merdeka framework. These differences are primarily influenced by teaching experience, educational background, professional development exposure, and adaptability to pedagogical innovation. Despite their differing approaches, both groups share a common goal of promoting meaningful and student-centered learning. The study highlights the importance of fostering intergenerational collaboration and differentiated professional training to bridge pedagogical gaps, enhance teacher adaptability, and sustain the implementation of deep learning practices responsive to the challenges of 21st-century education.